The Importance of Check-Cashing Businesses to the Unbanked: Racial/Ethnic Differences - Rhine, Sherrie L. W.; Greene, William H.; Toussaint-Comeau, Maude (The Review of Economics and Statistics, 2006)
The roughly 9.1% of all U.S. families that are without some type of transaction account (unbanked) are disproportionately represented among minorities. The unbanked often must rely on alternative ways to carry out basic financial transactions such as cashing payroll checks and paying bills. This study analyzes unique survey data and finds that a consumer's decision to patronize check-cashing businesses is jointly made with the decision to be unbanked. For the unbanked, these businesses are an important source of financial services. Attributes that contribute to these decisions, however, vary with the racial/ethnic group. Latent preference effects are also observed to influence this joint decision for blacks and Hispanics. These findings may explain in part why the provisions of the Debt Collection Improvement Act (DCIA) of 1996 have not been more successful in bringing unbanked federal benefits recipients into the financial mainstream. Consumer participation in mainstream financial markets can improve their ability to build assets and create wealth, can protect them from theft and discriminatory, predatory, or otherwise unsavory lending practices, and may promote economic stability and vitality in the communities where they reside. By more fully understanding consumers' financial decisions, policies can be better directed to improve the effectiveness of legislation such as the DCIA of 1996 in encouraging mainstream financial market participation.